Newton polytope of good symmetric polynomials - Nguyen, Duc-Khanh; Nguyen Thi Ngoc, Giao; Dang Tuan, Hiep; Do Le Hai, Thuy (Comptes Rendus. Mathématique)
We introduce a general class of symmetric polynomials that have saturated Newton polytope and their Newton polytope has integer decomposition property. The class covers numerous previously studied symmetric polynomials.